СОПОСТАВИТЕЛЬНОЕ ИЗУЧЕНИЕ ПРОЦЕССА ТЕРМИНООБРАЗОВАНИЯ В АНГЛИЙСКОМ И КАРАКАЛПАКСКОМ ЯЗЫКАХ - Авезимбетова, А.; Тенелбаев, Р. (SCIENCE and SOCIETY, 2018)
The article deals with the problems of the comparative study of the process of term building in different languages, namely, in the English and Karakalpak languages. The authors pay a great attention to terminological structures in these two languages and revealing specific and common word building elements analyzed in the work with the help of the method of componential analysis. Terminological formations in the article have been analyzed on the basis of morphological classification.
Keywords: root terms; financial documents; terminological structure; term formation; chemical terminology; special terminology